A systematic review of mental health and wellbeing outcomes of group singing for adults with a mental health condition. (2nd July 2018) - Williams, Elyse; Dingle, Genevieve A; Clift, Stephen
Abstract: Background: A growing body of research has found that participating in choir singing can increase positive emotions, reduce anxiety and enhance social bonding. Consequently, group singing has been proposed as a social intervention for people diagnosed with mental health problems. However, it is unclear if group singing is a suitable and effective adjunct to mental health treatment. The current paper systematically reviews the burgeoning empirical research on the efficacy of group singing as a mental health intervention. Methods: The literature searched uncovered 709 articles that were screened. Thirteen articles representing data from 667 participants were identified which measured mental health and/or wellbeing outcomes of group singing for people living with a mental health condition in a community setting. Results: The findings of seven longitudinal studies, showed that while people with mental health conditions participated in choir singing, their mental health and wellbeing significantly improved with moderate to large effect sizes. Moreover, six qualitative studies had converging themes, indicating that group singing can provide enjoyment, improve emotional states, develop a sense of belonging and enhance self-confidence in participants. Conclusion: The current results indicate that group singing could be a promising social intervention for people with mental health conditions. However, these studies had moderate to high risk of bias. Therefore, these findings remain inconclusive and more rigorous research is needed.